2018
DOI: 10.1080/15226514.2018.1460303
|View full text |Cite
|
Sign up to set email alerts
|

Compared the physiological response of two petroleum-tolerant contrasting plants to petroleum stress

Abstract: Petroleum not only benefits the world economy but also contaminates the soil. In order to select the plants tolerant to petroleum, the physiological response of two petroleum tolerant-contrasting plants, Mirabilis jalapa and Orychophragmus violace, were investigated in variation of petroleum-contaminated soils (0, 5, 10, 20, and 40 g petroleum per kg soil) for 120 d. Petroleum degradation rate, seeds germination rate, free proline, and superoxide dismutase and peroxidase activities of M. jalapa were higher tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…In our study, BP Diesel oil with Active technology had an explicitly negative effect on the growth and development of both grass species studied, i.e., Festuca rubra and Festuca arundinacea , and caused a significant decrease in their yield. The negative impact of petroleum-based products on plants was also reported by Kaur and Asthir (2015) and Ma et al (2018). The toxic effect of DO on Festuca rubra and Festuca arundinacea observed in the present study, as well as on other plant species (Pascale et al 2016; Olaranont et al 2018; Fatima et al 2018; Borowik and Wyszkowska 2018a; Khan et al 2018) is due to, among other things, disorders in the metabolism of organic compounds in plants (Ma et al 2018).…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…In our study, BP Diesel oil with Active technology had an explicitly negative effect on the growth and development of both grass species studied, i.e., Festuca rubra and Festuca arundinacea , and caused a significant decrease in their yield. The negative impact of petroleum-based products on plants was also reported by Kaur and Asthir (2015) and Ma et al (2018). The toxic effect of DO on Festuca rubra and Festuca arundinacea observed in the present study, as well as on other plant species (Pascale et al 2016; Olaranont et al 2018; Fatima et al 2018; Borowik and Wyszkowska 2018a; Khan et al 2018) is due to, among other things, disorders in the metabolism of organic compounds in plants (Ma et al 2018).…”
Section: Discussionsupporting
confidence: 73%
“…Soil contamination with petroleum-based products upsets its stability. Enzymes that take part in carbon, nitrogen, phosphorus, and sulfur metabolism are very good indicators of soil quality as they reliably depict soil condition in the real time (Adam and Duncan 1999; Wyszkowska et al 2006; Ma et al 2018; Nannipieri et al 2018). Their monitoring provides valuable information about soil health status (Borowik et al 2017; Wyszkowska et al 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the present study prove that DO exerted a stronger toxic effect on Elymus elongatus than P did. Also, investigations conducted by other authors [5,6,73,86,88] have demonstrated that petroleum products negatively affect the growth and development of plants such as Zea mays, Avena sativa, Lupinus luteus, Vulpia myuros, and Phalaris arundinacea. Although in our study the negative impact of DO diminished with time (since soil contamination) and that of P remained stable throughout the growing season, the soil polluted with these substances was characterized by a low capability of returning to the equilibrium state.…”
Section: Discussionmentioning
confidence: 99%
“…Proteins are responsible for transporting materials to and from the cell across the cell membrane. Proteins catalyze the reaction (enzymes), and they are important in energy transfer, respiration, photosynthesis, cellular communication, molecular recognition, and gene expression (Kessel and Ben, 2018); it is known that the protein content is an important indicator of the physiological status of plants (Ma et al, 2018), and many studies showed that the protein concentration decreased significantly with the increase in the oil concentration, including the decrease in the protein concentration in the Mirabilis Jalapa plant. With an increase in the concentration of crude oil in the soil (Ma et al, 2018), the study showed by Alzurfi et al (2019) a significant decrease in the protein values of Hydrilla verticillata , plant when exposed to different concentrations of crude oil (0.2, 0.1, 0.05, 0.01)% for a period of 24 days.…”
Section: Introductionmentioning
confidence: 99%